A method for preparing M13 or pUC libraries for sequencing DNA with high G + C or A + T contents - Vlcek, C; Paces, V (Gene, 1995)
A simple method is described to generate M13 or pUC libraries from DNA with a very high G + C or A + T content. The G + C-rich DNA is partially digested with HinPI or HpaII restriction enzymes and cloned into the vector linearized in its multiple cloning site with AccI. The A + T-rich DNA is partially digested with TspI and cloned into the EcoRI-linearized vector. These libraries are suitable for large-scale DNA sequencing.
Keywords: zastoupení bazí; sekvenční analýza DNA; Base Composition; genová knihovna; Sequence Analysis, DNA; Gene Library